Synergistic Effects of Combined Herbal Extracts on Immunological and Physiological Markers in Alloxan-Induced Diabetic Mice - Hammadi, Mahdi H. (American Journal of Biology and Natural Sciences, 2026)
Background: Diabetes mellitus is characterized by metabolic dysregulation, oxidative stress, and chronic inflammation. Recently, natural products have gained considerable attention as complementary therapeutic agents. Objective: This study aimed to evaluate the synergistic effects of cinnamon, turmeric, and fenugreek extracts on metabolic, oxidative, and immunological parameters in alloxan-induced diabetic mice. Methods: Male mice were allocated into control, diabetic, metformin-treated, herbal-treated, and combined treatment groups. Diabetes was induced using alloxan, and treatments were administered orally for 28 days. Fasting blood glucose, insulin, lipid profile, hepatic and renal function markers, oxidative stress indices, and inflammatory cytokines (TNF-α, IL-6, CRP, and IL-1β) were assessed. Data were analyzed using one-way ANOVA. Results: Diabetic mice showed significant increases in blood glucose, lipid profile, liver and kidney enzymes, oxidative stress markers, and pro-inflammatory cytokines (P < 0.01), accompanied by impaired antioxidant activity. Treatment with the herbal combination significantly improved glycemic control, reduced oxidative stress, and suppressed inflammatory mediators compared with untreated diabetic mice (P < 0.01). Notably, the combined herbal formulation demonstrated comparable or superior efficacy to metformin in several parameters. Conclusion: The combined extracts of cinnamon, turmeric, and fenugreek exhibit potent antidiabetic, antioxidant, and immunomodulatory properties, highlighting their potential as promising complementary therapeutic agents in diabetes management.